1998
DOI: 10.2166/wst.1998.0731
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of contaminants in relation to dredging operations in a mesotidal estuary (Tagus estuary, Portugal)

Abstract: During the construction of a New Bridge over the Tagus estuary 2.5 million tons of sediments were dredged, part of this quantity being contaminated material. The extension and intensity of the water turbidity associated with dredging operating varied with the tidal conditions but the resuspended material collected near the bucket dredger did not present a concentration increment in metals and PCB, when compared to the estuarine suspended sediments. The calculated distribution coefficients suggest that some con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…Other research shows that organic contaminants have more complex desorption processes (e.g. due to hydrophobicity), still enhanced by turbation (Vale et al 1998;Hellou et al 2005). This information supports the presented data and confirms the importance of assay conditions during sediment tests.…”
Section: Discussionmentioning
confidence: 99%
“…Other research shows that organic contaminants have more complex desorption processes (e.g. due to hydrophobicity), still enhanced by turbation (Vale et al 1998;Hellou et al 2005). This information supports the presented data and confirms the importance of assay conditions during sediment tests.…”
Section: Discussionmentioning
confidence: 99%
“…2). Further, it has one of the largest estuaries in Europe, with an area of roughly 320 km 2 formed by several channels and islands (Vale et al, 1998) being connected to the sea by a relatively narrow channel (ca. 2 km width).…”
Section: Study Areamentioning
confidence: 99%
“…Regardless the economic importance of the dredging activities throughout the world, it has been shown that dredging causes serious impacts, threatening ecosystems and their biological communities, particularly in areas where dredged sediments are contaminated (Sturve et al, 2005;Vale et al, 1998). This contamination is a serious problem, because harbors are frequently located on urban and industrial coasts, within wave-protected areas, where the conditions for the accumulation of a myriad of contaminants are ideal.…”
Section: Introductionmentioning
confidence: 99%